Informal communication and occupation in the Polish borderlands - Paszko, Izabela, author.
1 online resource (388 pages)
Keywords: The book explores the neglected role and social dynamics of informal communication - interpersonal channels not controlled ""from above"" - in the region of Upper Silesia under the German occupation during the Second World War (1939-1945).